A cost-effective FRCM technique for seismic strengthening of minarets. (15th February 2021) - Bayraktar, Alemdar; Hökelekli, Emin
Highlights: Cost-effective seismic strengthening technique based on Fabric Reinforced Cementitious Matrix (FRCM) for masonry brick and stone, and reinforced concrete minarets. 3D finite element models of minarets with and without strengthening considering the minaret-foundation-soil interaction with infinite element and contact. Nonlinear behaviors of masonry units, concrete, soil and FRCM materials. Abstract: Many collapses or severe damages in minarets occur due to large structural deformations during earthquakes. Minarets, which are part of the cultural heritage, require particular attention and appropriate methodologies for their strengthening. The present study proposes a cost-effective seismic strengthening technique, which includes minimal intervention, better workability and reduced cost, for brick-masonry, stone-masonry and Reinforced Concrete (RC) minarets. Fabric Reinforced Cementitious Matrix (FRCM) composites are used in the proposed strengthening technique. 3D finite element models of the minarets with and without strengthening are created considering the minaret-foundation-soil interaction with infinite elements. The nonlinear behaviors of masonry units, concrete and soil materials are modeled using Concrete Damage Plasticity (CDP) and Mohr-Coulomb failure models. The idealized stress-strain diagram for FRCM composite is considered in the analyses. Tie contact is considered between the soil-foundation and FRCM composite layer-wall interfaces. Three earthquake acceleration records selected for the nonlinear seismic analyses are matched to the target response spectrum, and the deconvolved acceleration records are obtained from the matched records. The nonlinear seismic analyses of brick-masonry, stone-masonry and concrete minarets with and without strengthening are implemented under the combined horizontal and vertical ground motions.